Perlindungan Dan Pemberdayaan Pasar Tradisional - Tarihoran, Sri Dewi (Jurnal El-Thawalib, 2022)
Based on the background above, the purpose of this study was to find out how the implementation of Regional Regulation Number 7 of 2016 Article 5 concerning the Protection and Empowerment of Traditional Markets on Traders in Sibolga City and also the Inhibiting Factors Implementation of Perda No. 7 of 2016 Article 5 on Protection and Market Empowerment Traditional on traders in Sibolga City. The type of research used by researchers is descriptive qualitative research, the data used is primary and secondary data, data collection methods with observation, interviews and documents. Data collected in analysis using editing, verification and analysis methods. Based on the results of the research above, the results are obtained that the implementation of Perda No. 7 of 2016 Article 5 concerning the Protection and Empowerment of Traditional Markets on Traders in Sibolga City has not been implemented maximally due to several factors, namely the lack of 50 civil service police personnel of Sibolga City To oversee / curb street vendors, facilities are inadequate and less comfortable for buyers, agricultural products are very minimal (such as fruits and vegetables), it is difficult to reach and the people are lazy to buy in the area and the people of Sibolga City dit the situation Nature where many Sibolga city income comes from working as fishermen.